Neutralization of coral snake Micrurus nigrocinctus venom by a monovalent antivenom - Gutiérrez, José María (1991)
The neutralizing ability of a monovalent anti-Micrurus nigrocinctus (coral snake) antivenom produced in Costa Rica was tested against the lethal, myotoxic and phospholipase A2 activities of homologous venom. In addition, immunodiffusion and Western blot analyses were performed. 2. In experiments where venom and antivenom were incubated prior to the test, antivenom was effective in neutralizing lethal, myotoxic and phospholipase A2 activities, with Effective Doses 50% of 2700 microliters antivenom/mg venom, 1840 microliters antivenom/mg venom, and 3630 microliters antivenom/mg venom, respectively. 3. When coral snake antivenom was administered at different times after coral snake venom injection, neutralization of lethality was achieved when antivenom was injected i.v. immediately and 15 min after venom. In contrast, lethality was not reduced when antivenom was administered by the im route. Only partial neutralization of myotoxicity was observed even when antivenom was injected i.v. immediately after envenomation. 4. Immunodiffusion and immunoblot analyses demonstrated the presence of antibodies in antivenom against several, but not all, venom components.